Tata Kelola Analisis Tingkat Kepuasan Mahasiswa Terhadap Tata Kelola E-learning Menggunakan Framework COBIT 5 Pada ITB Stikom Bali - Saragih, Hairunnisa; Indriyani, I. (Universitas Komputer Indonesia, 2024)
using the COBIT 5.0 framework. E-learning is an innovation in education that utilizes information technology to support the teaching and learning process flexibly. However, the success of its implementation is highly dependent on the level of user satisfaction, especially students. This research uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to 40 active students who have used the e-learning system for at least one semester. The results showed that the majority of students gave a positive assessment of e-learning services, especially in the Monitor, Evaluate, and Assess (MEA) domain. Nevertheless, there are some aspects that need to be improved, such as performance feedback and technical support, to enhance students' learning experience. This research is expected to contribute to the development of better e-learning governance in educational institutions. Keywords – Framework COBIT 5; E-Learning; Student Satisfaction.